When Agility Meets Engagement: Unveiling The Mechanism Of Employee Performance Enhancement - Irawati; Puspa Dewi; Ivalaina Astarina; Tomy Fitrio (Lembaga Publikasi Ilmiah Nusantara, 2026)
This study aims to develop a conceptual model of workforce agility, learning agility, and employee performance in Regional-Owned Enterprises (BUMD) in Indragiri Hulu Regency, with employee engagement as a mediating variable. Previous studies have reported inconsistent findings regarding the effect of workforce agility on employee performance and have generally examined workforce agility and learning agility separately. This study addresses this gap by integrating both constructs into a single model. A cross-sectional survey was conducted using a 5-point Likert-scale questionnaire administered to all employees of BUMD in Indragiri Hulu Regency, resulting in 169 respondents. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.1. The results show that workforce agility has no direct effect on employee performance, whereas learning agility does. Employee engagement mediates the relationships between workforce agility, learning agility, and employee performance. The novelty of this study lies in integrating workforce and learning agility with employee engagement as a mediating variable in the BUMD context. The findings extend the Job Demands-Resources Theory and Dynamic Capabilities Framework by highlighting employee engagement as a key mechanism linking agility and performance. Practically, BUMD managers should strengthen employee engagement and continuous learning to improve organizational adaptability and employee performance.